Terapi Behavior Dengan Metode Reward And Punishment Dalam Meningkatkan Kedisiplinan Anak Panti Asuhan Yos Sudarso - Salsabila Zahra; Salwa Sabilah; Kinanti Putri Herlambang (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to improve the discipline of orphanage children in obeying the rules by using behavior therapy in the Reward and Punishment method. The subjects of this research were orphanage children at the Yos Sudarso Orphanage. Meanwhile, the object of this research is the activities of orphanage children in the form of daily life in the orphanage. The data collection technique in this research uses a qualitative descriptive approach through questionnaires, observation, interviews and documentation. And the results of this research show that the use of the Reward and Punishment method can improve the discipline of orphaned children in their daily life at the orphanage.